Similes, metaphors, and creativity - Kao, Chen-Yao (Educational psychology (Dorchester-on-Thames), 2022)
This research aimed to examine the differential effects of simile and metaphor on creativity. In the main study, 123 participants were recruited from a university in Taiwan. A within-subjects experimental design was used to investigate how variables related to simile and metaphor influenced these participants' fluency and originality scores. As revealed by the findings, typical placements had an advantage over atypical placements in both fluency and originality scores whether the stimulus word pairs were conventional or novel. Similes, compared with metaphors, did not register significantly higher fluency or originality scores when conventional word pairs were provided. However, similes posted significantly higher fluency and originality scores than did metaphors when novel word pairs were provided. It can be also inferred that simile combined with the typical placement, especially in the context of novel word pairs, led to better performance on creativity than all the other combinations.